Analisis Perbandingan Metode Certainty Factor dan Teorema Bayes untuk Mendiagnosa Penyakit Autis Pada Anak - Ramadhanu Ginting; Muhammad Zarlis; Rika Rosnelly (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
This study discusses the design of a system that specifically addresses the problem of autism in children. Autism is a behavior that occurs to a person, especially a child, which makes social interaction difficult. The expert system is a system that represents the ability of an expert into a machine, where in this study, it discusses how to analyze 2 methods in an expert system, namely the Certainty Factor and the Bayes Theorem for diagnosing autism in children which aims to determine which method is the most appropriate and good to use. or implemented into an application. which will be useful later in determining the category of children with autism. Based on the research conducted by the author, a simple description of the comparative analysis of the Certainty Factor and Bayes Theorem methods is obtained where the Certainty Factor method has a calculation accuracy above 90%.